Zdravljenje zmrzlin s hiperbarično oksigenacijo - poročilo z odprave Si.mobil Ski Everest 2000 - Jaki, Polona (Medicinski razgledi, 2002)
Freezing cold injury (FCI), commonly known as frostbite, is a local injury of peripheral tissues caused by freezing. Its main pathophysiological mechanism is arterial vasoconstriction and hypoxia of peripheral tissues. Hyperbaric oxygenation (HBO) enhances oxygen supply to reversibly damaged tissues. This article is a case report of frostbite management with HBO therapy.
Keywords: poškodbe; zmrzline; prsti; therapy; zdravljenje; hiberbarična oksigenacija